The Convergence of Health Care Financing Structures: Empirical Evidence from OECD-Countries - Andrea Leiter; Engelbert Theurl (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
In this paper we concentrate on the question whether the financing structure of the health care systems converges. In a world of increasing economic integration convergence in health care financing (HCF) and, hence, decreasing differences in HCF across countries enhance individuals (labour) mobility and support harmonization processes. As an indicator for convergence we take the public financing ratio in % of total HCF and in % of GDP. The major finding is that HCF in the OECD countries converged in the time period 1970 2005. This conlusion also holds when looking at smaller sub groups of countries and shorter time periods. However, we find evidence that countries do not move towards a common mean and that the rate of convergence is decreasing over time.
Keywords: I11; I18; H55; 330; Convergence; health care system; health care financing